Prioritization in medicine: an international dialogue - Nagel, Eckhard; Lauerer, Michael (Springer International Publishing, 2016)
The gap between a rising demand for health care services on the one side and scarce resources on the other, is leading to a growing pressure on decision-making processes. Hence, prioritization in medicine has become an increasingly important issue for assuring stability of health systems and improving the capability of health care. The present volume addresses normative dimensions of methodological and theoretical approaches, the legal basis behind priority setting as well as international experiences concerning the normative framework and the process of priority setting. It also examines specific criteria for prioritization and discusses economic evaluations. Contributing authors from a broad range of scientific disciplines discuss prioritization within an international dialogue